Effectiveness Analysis Of Centrifugal Pump Maintenance System For Performance Optimization At Pt. Sumber Air Abadi - pratama, yuki alvandi; Manullang, Togu Juliaman; Wibisono, Muhammad Umar; Ditoswar, Arya Mahadika; hasibuan, Fardin (Universitas Riau Kepulauan, 2025)
This paper analyzes the centrifugal pump maintenance system and its impact on the effectiveness of pump performance at Perusahaan Sumber Air Abadi. The study identifies current maintenance practices, evaluates their effectiveness in preventing failures and optimizing pump operation, and proposes improvements for better system reliability and efficiency. Data were collected from maintenance records, pump performance, and personnel interviews. The findings indicate key areas for improvement in preventive maintenance scheduling, spare parts management, and personnel training. Implementation of these recommendations is expected to improve pump performance, reduce downtime, and contribute to the company's overall operational efficiency. The main focus is on the transition to a proactive maintenance culture through technology adoption and continuous skills development.